Role of mRNA expression of interleukin-6 and interleukin-10 in idiopathic preterm birth - Nayan, Deepika; Guleria, Kiran; Sharma, Tusha; Banerjee, B. D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: India is one of the nation’s leading in number of preterm births (PTB), as reported by WHO. Despite extensive research the exact cause of PTB remains elusive. The present study was designed to study the effect of inflammatory genes (proinflammatory IL-6 and anti-inflammatory IL-10) in etiopathogenesis of idiopathic PTB. Methods: Maternal blood and placental tissue samples of PTB cases (n=263) and equal number of term delivery controls (n=263) were collected at the time of delivery. mRNA expression of IL-6 and IL-10 gene was analysed using Real-time PCR. Results: mRNA expression of IL-6 gene (pro-inflammatory) was 11.73 folds high in maternal blood and 2.60 folds higher in placental tissue in PTB compared to term birth cases. mRNA expression of IL-10 gene (anti-inflammatory) was 25 folds lower in maternal blood and 10 folds lower in placental tissue of PTB compared to term deliveries. Conclusions: Interleukins have been identified to have a major role in etiopathogenesis of idiopathic preterm birth.